2006
DOI: 10.1093/jnci/djj133
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of ZSTK474, a New Phosphatidylinositol 3-Kinase Inhibitor

Abstract: ZSTK474 is a new PI3K inhibitor with strong antitumor activity against human cancer xenografts without toxic effects in critical organs. ZSTK474 merits further investigation as an anticancer drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
285
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 361 publications
(297 citation statements)
references
References 42 publications
10
285
1
1
Order By: Relevance
“…Recently, it has been shown that a pan-class IA PI3K inhibitor ZSTK474 [2-(2-difluoromethylbenzimidazol-1-yl)-4,6-dimorpholino-1,3,5-triazine], which was originally developed as an anticancer drug, (53) has a suppressive effect on inflammation and osteoclasts in collageninduced arthritis model, (54) suggesting that inhibition of class IA PI3K is a promising strategy for the rheumatoid arthritis therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a pan-class IA PI3K inhibitor ZSTK474 [2-(2-difluoromethylbenzimidazol-1-yl)-4,6-dimorpholino-1,3,5-triazine], which was originally developed as an anticancer drug, (53) has a suppressive effect on inflammation and osteoclasts in collageninduced arthritis model, (54) suggesting that inhibition of class IA PI3K is a promising strategy for the rheumatoid arthritis therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the ongoing clinical evaluation on these PI3K inhibitors is expected to furnish a new class of molecular targeted anticancer drugs. [11] . (C) Lineweaver-Burk plot analysis of inhibition of PI3Kα by ZSTK474 [64] .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, ZSTK474 inhibited the growth of 39 human cancer [11] , ( Figure 4A) and blocked cell cycle progression at G 0 /G 1 phase in various human cancer cells without obvious induction of apoptosis [11,66] . The G 0 /G 1 arrest effect might be attributed to inactivation of cyclin D1, enhanced expression of p27, and the following pRB dephosphorylation [66] .…”
Section: Pi3k a Promising Molecular Target For Cancer Chemo Therapymentioning
confidence: 97%
See 2 more Smart Citations